Determinants of cerebral hemodynamics during the Trail Making Test in schizophrenia - Schüpbach, Daniel; Egger, Stephan T.; Boeker, Heinz; Duschek, Stefan; Vetter, Stefan; Seifritz, Erich; Herpertz, Sabine (Brain and cognition, 2016)
Patients with schizophrenia show deficits in cognitive functioning, and studies on cerebral hemodynamics have revealed aberrant patterns of mean cerebral blood flow velocity (MFV), an equivalent of cerebral blood flow (CBF). Therefore, we carried out a controlled study that assessed MFV in schizophrenia during a well-known neuropsychological task, the Trail Making Test (TMT). We measured MFV in the middle cerebral arteries using functional transcranial Doppler sonography in 15 schizophrenia patients and 15 healthy subjects.